Effect of niobium promoter on iron-based catalyst for Fischer-Tropsch reaction - Ali, S. (Elsevier, 2012)
In the present work, we have modified Fe/CNTs catalysts with niobium. The catalysts were prepared using a wet impregnation method and promoted with niobium. Samples were characterized by nitrogen adsorption, H2-TPR, TPD, XRD and TEM. The Fischer-Tropsch Synthesis (FTS) was carried out in a fixed-bed microreactor at 220°C, 1 atm and H2/CO=2 for 5h. Addition of niobium into Fe/CNTs increased the dispersion, decreased the average size of iron oxide nanoparticles and the catalyst reducibility. Niobium-promoted Fe catalyst resulted in appreciable increase in the selectivity of C5+ hydrocarbons and suppressed methane formation. These effects were more pronounced for the 0.04%Nb/Fe/CNTs catalyst, compared to those observed from other niobium compositions. The 0.04%Nb/Fe/CNTs catalyst enhanced the C5+ hydrocarbons selectivity by a factor of 67.5% and reduced the methane selectivity by a factor of 59.2%.